An Electric‐Field‐Reinforced Hydrophobic Cationic Sieve Lowers the Concentration Threshold of Water‐In‐Salt Electrolytes. Issue 47 (13th October 2022) - Zhou, Anxing; Zhang, Jinkai; Chen, Ming; Yue, Jinming; Lv, Tianshi; Liu, Binghang; Zhu, Xiangzhen; Qin, Kun; Feng, Guang; Suo, Liumin
Abstract: High‐concentration water‐in‐salt (WIS) electrolytes expand the stable electrochemical window of aqueous electrolytes, leading to the advent of high‐voltage (above 2 V) aqueous Li‐ion batteries (ALIBs). However, the high lithium salt concentration electrolytes of ALIBs result in their high cost and deteriorate kinetic performance. Therefore, it is challenging for ALIBs to explore aqueous electrolytes with appropriate concentration to balance the electrochemical window and kinetic performance as well as the cost. In contrast to maintaining high concentrations of aqueous electrolytes (>20 m), a small number of hydrophobic cations are introduced to a much lower electrolyte concentration (13.8 m), and it is found that, compared with WIS electrolytes, ALIBs with these concentration‐lowered electrolytes possess a compatible stable electrochemical window (3.23 V) and achieve better kinetic performance. These findings originate from the added cations, which form an electric‐field‐reinforced hydrophobic cationic sieve (HCS) that blocks water away from the anode and suppresses the hydrogen evolution reaction. Meanwhile, the lower electrolyte concentration provides significant benefits to ALIBs, including lower cost, better rate capability (lower viscosity of 18 cP and higher ionic conductivity of 22 mS cm −1 at 25 °C), and improved low‐temperature performance (liquidus temperature of −10.18 °C). Abstract : A small number of hydrophobic cations are introduced to appropriate concentration electrolyte (ACE) (13.8 m). The added cations can form an electric‐field‐reinforced hydrophobic cationic sieve (HCS) that blocks water away from the anode and suppresses HER. Thus, the ALIBs with HCS‐ACE can possess a compatible stable electrochemical window and achieve lower cost and better kinetic performance.